Evaluation of three‐dimensional superimposition technique on parietal bone of the puberty beagle dogs. (20th August 2018) - Yang, Xin; Xiao, Chang; Liu, Fen; Jian, Fan; Yang, Li'an; Nie, Hong; Wu, Jianyong
Abstract: Objectives: This study aimed to (a) evaluate the stability of the parietal bone of 6–9 months old beagles and (b) examine whether parietal regional superimposition can provide an atraumatic and effective solution for further maxillary expansion study. Materials and Methods: Six prepubertal 6‐month‐old male beagles were included. Six miniscrew markers were inserted into the left and right sides of the parietal bone, and two of them were placed bilaterally near the palatal suture. The subjects were scanned with cone beam computed tomography (CBCT) at three time points of T 0 (6 months old), T 1 (7.5 months old) and T 2 (9 months old), respectively. All skull models were analyzed by both the miniscrew superimposition and the parietal regional superimposition. Results: The two superimposition methods had no significant difference ( p > 0.05) in displacements of miniscrew markers between left and right first premolars (PM1). The maxillary superimposition between T 0 and T 2 indicated that the length and width of the maxillary as well as the width of the zygoma root increased significantly ( p < 0.05), while the height of maxillary had no significant difference ( p > 0.05) over the 3 months. Conclusions: The parietal bone is relatively stable for beagles from 6 months old to 9 months old and thus can be used as a reference region for 3D skull model superimposition of the beagle dog.